1993
DOI: 10.1002/eji.1830230931
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic tail of the T cell receptor ζ chain is dispensable for antigen‐mediated T cell activation

Abstract: The T cell antigen receptor consists of an antigen-binding alpha beta heterodimer and a group of invariant polypeptides denoted CD3-gamma, CD3-delta, CD3-epsilon and CD3-zeta. Whether antigen responsiveness is dependent on the expression of functional CD3-zeta subunit remains controversial. For instance, transfection of a zeta-/eta- variant of the 2B4.11. T cell hybridoma with mutated zeta cDNA that encoded a zeta protein truncated at residue 108, restored the surface expression of T cell antigen receptor comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…Analysis of chimeric receptors containing internalization signals from the cytoplasmic domains of CD3␥ and CD3␦ have shed light on a possible role for whereby it masks internalization signals present in the TCR complex from the cellular endocytic machinery (28,34). Consistent with this masking role, reports on the ability of C-terminal deletion or internal deletion mutants of in cell lines and transgenic mice to support TCR expression have indicated that the extent of deletions of the native sequence correlates with reduced ability to support surface expression (7,(35)(36)(37).…”
Section: Sequence-independent Regulation Of Surface Tcr Levels Bymentioning
confidence: 84%
“…Analysis of chimeric receptors containing internalization signals from the cytoplasmic domains of CD3␥ and CD3␦ have shed light on a possible role for whereby it masks internalization signals present in the TCR complex from the cellular endocytic machinery (28,34). Consistent with this masking role, reports on the ability of C-terminal deletion or internal deletion mutants of in cell lines and transgenic mice to support TCR expression have indicated that the extent of deletions of the native sequence correlates with reduced ability to support surface expression (7,(35)(36)(37).…”
Section: Sequence-independent Regulation Of Surface Tcr Levels Bymentioning
confidence: 84%
“…Moreover, the transgene-encoded TCR does not provide for the alloreactivity of the T cells that bear it; alloreactivity comes instead from receptors selected on the H-2b background in this case, and these are likely to be both self-MHC-restricted and alloreactive, as is true of several other TCR that have been shown to have similar dual specificity. Studies using clonotypic antibodies to block a given TCR (11,12) as well as transfection data (13)(14)(15)(16)) have yet to reveal cells that have two TCRs that mediate recognition of antigen and self-MHC separately from recognition of non-self-MHC. Indeed, it appears from these studies that, in each case, alloreactivity involves cross-reactions of TCR specific for a foreign antigenic peptide bound to self-MHC molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To further examine the development of T cells with two TCRs, we have analyzed CD4+ T cells in mice transgenic for the rearranged genes encoding the a and 13 chains of an autoreactive TCR specific for myelin basic protein (MBP) and the MHC class II molecule I-Au (3). This system has allowed us to examine the expression of TCRs of two different types on a single cell and to ask directly whether T cells having two different TCRs are required for the development of autoimmunity.…”
mentioning
confidence: 99%
“…The disulfide-linked ca3 heterodimer is responsible for antigen recognition (Dembic et al, 1986;Saito et al, 1987b) and the activation signals are delivered through the associated CD3 chains (Malissen and Schmitt-Verhulst, 1993). Recent studies have provided definitive evidence for a signal transduction function of the CD3E and r chains Romeo and Seed, 1991;Letourneur and Klausner, 1992a;Wegener et al, 1992;Hermans and Malissen, 1993); however, the specific role of the CD3-y and 6 chains in TCR function is still unknown. After TCR stimulation, a number of cellular proteins become phosphorylated on tyrosine residues, among them being r (Baniyash et al, 1988), ZAP-70 (Chan et al, 1991), the proto-oncogene vav (Margolis et al, 1992) and phospholipase C-yl (PLC'yl) (Park et al, 1991;Secrist et al, 1991;Weiss et al, 1991).…”
Section: Introductionmentioning
confidence: 99%